2022
DOI: 10.1101/2022.12.01.22283006
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SARS-CoV-2 infection- induced seroprevalence among children and associated risk factors during pre- and omicron-dominant wave, from January 2021 through November 2022, Thailand: Longitudinal study

Abstract: Background Severe acute respiratory syndrome-coronavirus-2 (SARS-CoV-2) infection can be asymptomatic in young children. Therefore, the true rate of infection is likely underestimated. Few data are available on the rate of infections in young children, and studies on the SARS-CoV-2 seroprevalence among children during omicron wave are limited. Our study aims to assess the SARS-CoV-2 infection-induced seroprevalence among children and estimated the associated risk factors for seropositivity. Methods A longitudi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“… 26 , 27 Studies were primarily done in high-income countries (eg, the USA, Canada, and Israel), and assessed a complete primary schedule of BNT162b2 vaccine (n=46 [90%]). Three (6%) studies only assessed the effect of a single dose of either BNT162b2 or mRNA-1273, 28 , 29 , 30 and nine (18%) studies assessed the effect of a monovalent 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 or bivalent (BNT162b2 bivalent [against original strain or omicron BA.4 or BA.5]) 39 booster vaccination ( appendix 1 pp 26–33 ). Participants' age was in line with the authorised age group (ie, 5–11 years for studies on BNT162b2 or BNT162b2 bivalent and 6–11 years for studies on mRNA-1273; appendix 1 pp 26–33 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 26 , 27 Studies were primarily done in high-income countries (eg, the USA, Canada, and Israel), and assessed a complete primary schedule of BNT162b2 vaccine (n=46 [90%]). Three (6%) studies only assessed the effect of a single dose of either BNT162b2 or mRNA-1273, 28 , 29 , 30 and nine (18%) studies assessed the effect of a monovalent 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 or bivalent (BNT162b2 bivalent [against original strain or omicron BA.4 or BA.5]) 39 booster vaccination ( appendix 1 pp 26–33 ). Participants' age was in line with the authorised age group (ie, 5–11 years for studies on BNT162b2 or BNT162b2 bivalent and 6–11 years for studies on mRNA-1273; appendix 1 pp 26–33 ).…”
Section: Resultsmentioning
confidence: 99%
“…As recommended in the ROBINS-I guidance, outcomes rated with a critical risk of bias were not included in data synthesis. 15 Excluded outcomes were SARS-CoV-2 infections in one study, 36 COVID-19-related hospitalisation in three studies, 27 , 40 , 41 ICU admissions in two studies, 27 , 41 deaths reported in one study, 41 and myocarditis in one study ( appendix 1 pp 34–36; appendix 2 ). 35 …”
Section: Resultsmentioning
confidence: 99%
“…The seroprevalence of antibodies against the N protein in Japan was reported to be 3.5% in February to March 2022 [1] and cumulative confirmed cases as of May 2023 exceeded 33.8 million (28.2% of the Japanese population). Unlike other countries where seroprevalence rates exceeded 50% [3, 4, 610], most of the Japanese population had not been infected at that time, suggesting the possibility of future SARS-CoV-2 epidemics in Japan.…”
Section: Resultsmentioning
confidence: 92%
“…The threat of SARS-CoV-2 is subsiding as most people have acquired sufficient antibodies through vaccination and/or infection to prevent severe COVID-19; more than 80% of the populations of major industrialized countries have antibodies against the S protein induced by vaccination and/or infection [1–5]. In contrast, the seroprevalence of antibodies against the N protein elicited by SARS-CoV-2 infection ranged from 44.4% to 80.2% in the United States, England, Spain, Slovenia, Switzerland, and Thailand between March and November 2022 after the emergence of the omicron variants [3, 4, 610]. The positive rate was higher among younger individuals than among the elderly [8].…”
Section: Introductionmentioning
confidence: 99%
“…[14] The increased prevalence of the disease after the omicron variant pandemic was also demonstrated in healthy Thai children. [15] While the patients infected with the omicron variant may be younger than the delta variant, [14] our patients’ ages were comparable in both periods of the pandemic.…”
Section: Discussionmentioning
confidence: 88%